Integrating community extension services into 21st-century health education delivery in Nigeria: Evidence from rural and underserved communities - J. Lakan Mohammed; Kingsley Ibadin; Katun Mohammed (Aminu Kano Academic Scholars Association Multidisciplinary Journal, 2026)
Persistent disparities in health access and outcomes continue to define the lived realities of many rural and underserved communities across Nigeria. Despite various policy interventions, gaps in health education delivery remain pronounced due to infrastructural deficits, workforce shortages, poverty, and sociocultural barriers. This study examines how integrating community extension services into 21st-century health education frameworks can enhance outreach, inclusiveness, and sustainability in Nigeria’s public health system. Adopting a mixed-methods design, the research combines quantitative survey data with qualitative interviews to provide a comprehensive understanding of community-level dynamics. A multi-stage sampling technique was used to select 600 respondents across six states representing Nigeria’s geopolitical zones, including community members, health extension workers, local health administrators, and civil society actors. Structured questionnaires generated quantitative data analyzed using descriptive and inferential statistics, while thematic analysis was applied to qualitative narratives to capture contextual realities and lived experiences. Findings reveal that community extension services significantly improve health literacy, preventive health behaviors, and trust in local health institutions when strategically integrated with digital tools, local leadership structures, and culturally responsive communication strategies. The study also highlights the importance of continuous training for extension personnel and the need for policy alignment between federal, state, and local governments. Importantly, communities where participatory engagement models were adopted recorded higher levels of awareness regarding maternal health, immunization, sanitation practices, and non-communicable disease prevention. The study concludes that a people-centered, technologically adaptive extension framework offers a viable pathway for strengthening health education delivery in Nigeria’s rural landscape. By repositioning community extension services as a core component of health system reform, Nigeria can move closer to equitable and sustainable healthcare access for marginalized populations.